2004
DOI: 10.1021/bm0400473
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Divide between the High- and Low-Solid Analyses in the Gelatin/κ-Carrageenan Mixture

Abstract: Over the past few years, a considerable amount of work has been done in several laboratories on the measurement of structural properties of low-solid biopolymer mixtures or high-solid materials of a single biopolymer in the presence of co-solute. The main objective of this work has been to establish a correlation between the two types of systems and extend it to a binary mixture in a high-solid environment. In doing so, it employed well-characterized kappa-carrageenan and gelatin samples in an aqueous preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Of particular relevance to the present study, the mechanical properties of composite biopolymer gels which are extensively investigated from theoretical and experimental view points (Clark, Richardson, Ross-Murphy, & Stubbs, 1983;Kasapis & Al-Marhoobi, 2005;Kasapis, Morris, Nortron, & Clark, 1993;Morris, 1992). More recently, Kontogiorgos, Ritzoulis, Biliaderis, and Kasapis (2006) investigated the rheological and structural properties of acid-set sodium caseinate gels containing b-glucan, and they showed that although the system phase separated, the rheology of the mixture is dominated by that of the protein network at low b-glucan concentrations (p3%).…”
Section: Article In Pressmentioning
confidence: 99%
“…Of particular relevance to the present study, the mechanical properties of composite biopolymer gels which are extensively investigated from theoretical and experimental view points (Clark, Richardson, Ross-Murphy, & Stubbs, 1983;Kasapis & Al-Marhoobi, 2005;Kasapis, Morris, Nortron, & Clark, 1993;Morris, 1992). More recently, Kontogiorgos, Ritzoulis, Biliaderis, and Kasapis (2006) investigated the rheological and structural properties of acid-set sodium caseinate gels containing b-glucan, and they showed that although the system phase separated, the rheology of the mixture is dominated by that of the protein network at low b-glucan concentrations (p3%).…”
Section: Article In Pressmentioning
confidence: 99%
“…Non-invasive mechanical measurements have to be conducted within the linear viscoelastic region (LVR) of the material, where the magnitudes of stress and strain are related linearly (Kasapis, 2004;Kasapis and Al-Marhoobi, 2005;Kasapis, 2006). Fig.…”
Section: Small Deformation Dynamic Oscillatory Measurementsmentioning
confidence: 99%
“…Segregative phase separation is driven by the Flory-Huggins interactions of polymer-polymer and polymer-solvent that are much more temperature dependent 35 , whereas associative phase separation usually originates from the relatively temperature-insensitive electrostatic interaction between polymers. Enhanced biopolymer compatibility at higher temperature is understandable, since the repulsive interactions 1 A "steeper" tie-line in the case of the pseudo-binary phase diagrams presented here actually corresponds to a less steep or more horizontal tie line in the true ternary phase diagram. between polymer neighbors tend to be weaker as temperature increases.…”
Section: Discussionmentioning
confidence: 81%
“…Considerable attention has been paid to the behavior of biopolymer mixtures due to their broad technological applications 1,2 . In the food industry, polysaccharide/polysaccharide and polysaccharide/protein mixtures are often used to control product properties and even to create "new" foods with desired texture and quality 3 .…”
Section: Introductionmentioning
confidence: 99%